The developing of tribotechnical organoplastic - Burya, O.I.; Kalinichenko, S.V.; Tomina., A.-M.V; Nachovniy, I.I. (Problems of Tribology, 2019)
It is known that polymeric materials, with a high level of operational properties, make it possible to solve a number of technical issues in a new way, aimed at improving the reliability of operation and increasing the service life of friction units of machines and mechanisms. First of all, this is explained by the fact that traditional materials (steel, cast iron, babbit, bronze, etc.) do not always meet the needs of modern engineering practice. Organic hardened polymer materials – organoplastics (OPs) – surpass steel, aluminum, and plastics due to their unique properties: high chemical resistance, low density (they are lighter than carbon and fiberglass plastics), and their ability to accumulate damage over time without forming a critical crack. OPs based on thermoplastic binders are widely used, some of the popular heat-resistant representatives of which are fluoropolymers – known for their exceptional resistance to chemicals and corrosion, temperature short-term heating to 533 K, and natural lubricity. The influence of the content of organic Talon T700 fiber on the tribological properties of organoplastics based on polytetrafluorethylene is considered. It is showed that in the conditions of friction without lubrication the introduction of filler has positive effect on output polymer: it decreases friction coefficient by на 15 - 40 % and reduces wear by two orders of magnitude (from 91,75 to 0,15). The developed composition can be used for manufacturing of the details of moving joints of machines and mechanisms which are used in different industrial spheres.